Upaya Peningkatan Kemampuan Guru Dalam Menyusun Perangkat Pembeajaran Melalui Kegiatan In House Training Pada Guru MGMP IPA Madrasah Tsanawiyah Kabupaten Sukabumi - Arifin, Widad (Nusantara: Jurnal Pendidikan Indonesia, 2021)
Problems that often arise in educational institutions are the difficulty of getting teaching staff according to their fields, the limited number of permanent teachers, the inexperience of teaching teachers and the limited infrastructure in madrasas. Completeness of learning according to the KKM is still low, ranging from 40-60%. One of the efforts made is conducting In-House Training activities for teachers in MGMP associations in the preparation of teaching equipment as supervisory action research (PTKP). The purpose of this study was to improve the ability of IPA MGMP teachers in Sukabumi district in compiling teacher learning tools and determine the right steps to improve the ability of teachers in compiling teaching completeness. The research was conducted on teachers who were assembled in the IPA MGMP of Sukabumi Regency for approximately 6 months starting from July s / d. December 2020. Data collection was carried out through questionnaires, observation and documentation. From the questionnaire, it was found that overall the teacher stated it was important to have teaching completeness. The research was conducted in 2 cycles. In Pre-PTKP, only 62.72% of teachers can arrange learning tools, then in the first cycle there is an increase to 68.38%, then in the second cycle, there is an increase of up to 86.52% and all teachers in the preparation of learning tools are GOOD or have intermediate values 76 s / d. 90. All teachers want In-House Training for the preparation of learning tools and 100% of teachers to have high motivation to take part in In-House Training and have a strong desire to make learning tools and will use these learning tools to support the learning process.